2017
DOI: 10.1128/aac.01666-17
|View full text |Cite
|
Sign up to set email alerts
|

The Global Regulatory Cyclic AMP Receptor Protein (CRP) Controls Multifactorial Fluoroquinolone Susceptibility in Salmonella enterica Serovar Typhimurium

Abstract: Fluoroquinolone antibiotics are prescribed for the treatment of infections, but resistance to this family of antibiotics is growing. Here we report that loss of the global regulatory protein cyclic AMP (cAMP) receptor protein (CRP) or its allosteric effector, cAMP, reduces susceptibility to fluoroquinolones. A Δ mutation was synergistic with the primary fluoroquinolone resistance allele , thus able to contribute to clinically relevant resistance. Decreased susceptibility to fluoroquinolones could be partly exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 67 publications
0
21
0
Order By: Relevance
“…Fluoroquinolones target DNA topoisomerases, and resistance requires amino acid changes to reduce antibiotic affinity for the topoisomerase called DNA gyrase. In most bacteria, including Enterobacteriaceae, clinical resistance to fluoroquinolones can only be achieved through the additive contributions of multiple genetic loci (Hooper 2001;Corkill et al 2005;Kary et al 2017;Osei Sekyere and Amoako 2017). Fluoroquinolones have a demonstrated ability to induce natural competence in Streptococcus (Prudhomme et al 2006); thus, antibiotic exposure increases the potential for HGT and consolidation of chromosomal resistance alleles.…”
Section: Horizontal Transfer Of Accessory Resistance Cassettes Comparmentioning
confidence: 99%
“…Fluoroquinolones target DNA topoisomerases, and resistance requires amino acid changes to reduce antibiotic affinity for the topoisomerase called DNA gyrase. In most bacteria, including Enterobacteriaceae, clinical resistance to fluoroquinolones can only be achieved through the additive contributions of multiple genetic loci (Hooper 2001;Corkill et al 2005;Kary et al 2017;Osei Sekyere and Amoako 2017). Fluoroquinolones have a demonstrated ability to induce natural competence in Streptococcus (Prudhomme et al 2006); thus, antibiotic exposure increases the potential for HGT and consolidation of chromosomal resistance alleles.…”
Section: Horizontal Transfer Of Accessory Resistance Cassettes Comparmentioning
confidence: 99%
“…Some studies have provided evidence that the "site" mutations of EF-G result in large changes in gene expression such as cyaA (adenylate cyclase) and topA (topoisomerase I) [24]. The topA gene acts jointly with topoisomerase IV genes (parC and parE) and relaxes DNA supercoils in opposition to GyrAB activity, while the GyrAB protein is the most important site to form the resistance of fluoroquinolone [21]. Previous studies have reported that the tetracycline (TC) antibiotics inhibit bacterial protein synthesis by preventing the attachment of aminoacyl tRNA to the ribosomal acceptor A site [50].…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that elongation factors play important roles in forming bonds between the tRNA attached peptidyltransferase and the next amino acid, ribosomal translation, causing premature dissociation of the peptidyl-tRNA from the ribosome and protein synthesis [16][17][18][19]. Previous studies have shown that elongation factors can not only inhibit bacterial protein synthesis using the antibiotics tetracycline, tylosin and fluoroquinolone [20,21], but also take part in imparting drug resistance in Escherichia coli. Moreover, elongation factors have been reported to be differentially expressed in tylosin-resistant Mycoplasma gallisepticum [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Cyclic AMP signalling, which is one of the best studied signalling pathways in biology, has been implicated in AMR 4,5 . Several earlier studies have linked cAMP signalling to antibiotic resistance in gram-negative bacteria 6,7 . For example, Alper et al .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Kary et al . reported that Salmonella typhimurium strains lacking Crp (a cAMP-activated global transcriptional regulator) or with altered levels of cAMP exhibit reduced susceptibility to fluoroquinolones as a result of decreased permeability and increased efflux of this class of antibiotics 7 .…”
Section: Introductionmentioning
confidence: 99%